Competing devotions in the postpandemic economy: the effect of remote working on perceptions of employees as “good workers” and “good parents” in Germany, South Korea, and the United States - Youngjoo Cha; Lena Hipp; Soocheol Cho (Social Forces, 2026)
Before the pandemic, remote workers were often perceived as less committed than their in-office counterparts. Have these perceptions persisted in the postpandemic era of global remote work expansion? Does working remotely affect how people are viewed as parents and not just as workers? How do these relationships differ across cultural contexts with different work and parenting norms? We address these questions using original, preregistered survey experiments in three countries with distinct work cultures and gender norms: Germany, South Korea, and the United States. In all three countries, remote workers are perceived as less committed to work but as better parents. These effects, however, differ across countries in gender-specific ways: when working remotely, South Korean fathers face larger penalties in perceived work commitment than fathers in Germany, and South Korean mothers receive larger parental rewards than mothers in both Germany and the United States. These findings suggest that workers face competing pressures from work and family, and that remote work can produce distinctively gendered outcomes—drawing mothers into remote work while pushing fathers away from it. However, this pattern only occurs in cultural contexts where work and parenting norms are strongly gendered, such as South Korea.
Keywords: 300; remote work; flexibility stigma; surve yexperiments